Development of evidence-based quality indicators for deep brain stimulation in patients with Parkinson's disease and first year experience of implementation of a nation-wide registry. (March 2019) - Haas, Kirsten; Stangl, Stephanie; Steigerwald, Frank; Matthies, Cordula; Gruber, Doreen; Kühn, Andrea A.; Krauss, Joachim K.; Sixel-Döring, Friederike; von Eckardstein, Kajetan; Deuschl, Günther; Classen, Joseph; Winkler, Dirk; et al.
Abstract: Introduction: Deep Brain Stimulation (DBS) is a complex, invasive and cost-intensive therapy that requires a high level of expertise. To date, data on quality of DBS in clinical routine in the German health care system are lacking. Methods: The development of evidence-based QIs for DBS in PD patients was performed following a standardized process by a multidisciplinary board between 2014 and 2016. The process was initiated by the German Parkinson Society and followed international recommendations for developing QIs including: a systematic literature search; an appraisal of the published evidence; a consensus-based selection of the QI set; and a pilot study to assess the feasibility in implementing the QIs in clinical routine. Results: A set of 28 QIs for determining the quality of DBS in PD was established by the board covering different dimensions of health care quality (structure, process, and outcome) in different treatment phases of DBS care (pre-operative, peri-operative, and post-operative). Implementation in clinical practice was tested in a pilot study comprising three hospitals delivering DBS care. The feasibility of the QI set was evaluated positively by the participating physicians and hospitals. Mean time to document one patient was 25 min. The German-wide implementation of the defined indicator set within a dedicated quality registry (QualiPa) started in June 2016. Conclusion: QIs are a necessary requirement to monitor hospital performance in DBS care. The evidence-based approach to develop the proposed indicator set is expected to assure transparency, acceptance and long-term applicability of the QI set in Germany. Highlights: No indicators for measuring quality of DBS care in clinical routine exist in Germany. In a standardized process key performance indicators covering different dimensions of quality of DBS care were identified. A set of 28 quality indicators (QI) was developed for DBS care. The QI set was implemented successfully in a Germany-wide registry.